2015
DOI: 10.1108/ijshe-01-2013-0005
|View full text |Cite
|
Sign up to set email alerts
|

Variation in sustainability competency development according to age, gender, and disciplinary affiliation

Abstract: Purpose -The purpose of this paper is to present the results of a classroom assessment aimed at determining the extent to which five key sustainability competencies develop in students during an introductory transdisciplinary sustainability course. University sustainability programs intend to provide integrated education that fosters the key competencies students need to solve real-world sustainability problems. Translating sustainability competencies into effective pedagogical practice in integrated academic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 86 publications
0
45
0
1
Order By: Relevance
“…Finally, a deeper concern exists regarding our preliminary work: our measuring of transdisciplinary skills may warrant strengthening. Assessment techniques described in the transdisciplinary literature (for example see [31,25] generally rely on the detailed and timeconsuming assessment of written work using a carefully constructed marking rubric. To avoid long assessment times, we chose here to focus on systems thinking as measured by Cmap scores.…”
Section: Discussion Of Data Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a deeper concern exists regarding our preliminary work: our measuring of transdisciplinary skills may warrant strengthening. Assessment techniques described in the transdisciplinary literature (for example see [31,25] generally rely on the detailed and timeconsuming assessment of written work using a carefully constructed marking rubric. To avoid long assessment times, we chose here to focus on systems thinking as measured by Cmap scores.…”
Section: Discussion Of Data Collection and Analysismentioning
confidence: 99%
“…More traits than those in Table 1 are mentioned in the literature [8,31,32]. In particular, Remington-Ducette and Musgrave [25] describe interpersonal competence as a component of transdisciplinarity, and, as part of this competence, include the characteristic of empathy. Walther et al [29] report a model of empathy in engineering practice that includes traits of self and other awareness, affective sharing, perspective-taking, and emotional regulation.…”
Section: Bernstein (2015) [2]mentioning
confidence: 99%
“…Outcomes: Most of the program evaluations included in the articles demonstrated or claimed positive effects on student/teacher learning related to ESD. Among these, five studies focused on teaching and learning assessment of ESD demonstrated a statistically significant effect [22,27,32,35,36], while three other studies focused on teacher education in the areas of ESD demonstrated the same [29,33,37]. For instance, some of these studies found that ESD courses strongly impacted participants' positive beliefs, norms and attitudes towards sustainable development [29,37].…”
Section: Strengths and Weaknesses Of Assessment Approachesmentioning
confidence: 99%
“…However, the author explained that this was mainly because the program design was not specifically for pre-service teachers [28]. It is also noteworthy that one assessment suggested that ESD-related competencies were developed differently among university students according to gender, disciplinary, affiliation and age [36]. For instance, as a result of the same ESD course, interpersonal competencies improved more among female students than male students, and normative orientation improved only among younger students [36].…”
Section: Strengths and Weaknesses Of Assessment Approachesmentioning
confidence: 99%
“…Managerial competencies can be used to attain the desired sustainable development outputs (Chung et al, 2016;Dudin et al, 2017;Dumitrescu, et al, 2014;Dzhengiz & Niesten, 2019;Mukhopadhyay et al, 2011;Remington-Doucette & Musgrove, 2015). This indicates that having a manager with robust managerial competencies is essential to complete sustainable development projects.…”
Section: Introductionmentioning
confidence: 99%